"We're really not ready for this": A qualitative exploration of community pharmacy personnel's perspectives on the pharmaceutical care of older people with sensory impairment. Issue 2 (April 2019) - Alhusein, N.; Killick, K.; Macaden, L.; Smith, A.; Stoddart, K.; Taylor, A.; Kroll, T.; Watson, M.C.
Abstract: Background: In most developed countries there is an increasing ageing population living in the community with long-term conditions and sensory impairment (sight; hearing; dual impairment). Community pharmacy personnel are key providers of pharmaceutical care to this patient population. Objective: This study explored community pharmacy personnel's experiences with providing pharmaceutical care for older people with sensory impairment. Methods: Semi-structured telephone interviews were conducted with community pharmacy personnel across Scotland between 2015 and 2016. Results: Thirty interviews were completed with community pharmacists (n = 17) and other pharmacy personnel (n = 13). Two overarching themes emerged: safety and communication. Interviewees reported patients' reluctance to disclose their impairment "patients are very good at hiding it" and had considerable safety concerns " it's a fear that they're going to take too much … accidentally taking the same medicine twice ". Difficulties in communication were cited " no matter what you do or how you label things, leaflets and telling people, things can go wrong ". Additionally, interviewees identified training needs to increase their disability awareness and to identify strategies to provide safe and reliable pharmaceutical care to this vulnerable group "We don't specifically have anything in place to deal with anyone with impairments of that kind". Conclusions: This is the first in-depth exploration of providing pharmaceutical care to older people with sensory impairment from the perspective of community pharmacy personnel. Strategies are needed to encourage older people to disclose their sensory impairment. Education and training are also needed to optimise the provision of pharmaceutical care to this vulnerable population.